1975
DOI: 10.1152/jappl.1975.39.2.305
|View full text |Cite
|
Sign up to set email alerts
|

A modified measurement of respiratory resistance by forced oscillation during normal breathing

Abstract: We have modified the measurements of the resistance of the respiratory system, Rrs, by the forced oscillation technique and we have developed equipment to automatically compute Rrs. Flow rate and mouth pressure are treated by selective averaging filters that remove the interference of the subject's respiratory flow on the imposed oscillations. The filtered mean Rrs represents a weighted ensemble average computer over both inspiration and expiration. This method avoids aberrant Rrs values, decreases the variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
1

Year Published

1981
1981
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
3
8
1
Order By: Relevance
“…The course of resist ance was independent of frequency, in agreement with other authors [21,27]. In our patients with obstructive lung diseases frequency dependence of resistance in creased with the degree of airway obstruc tion, a phenomenon also observed by others [8,14,18,21,27). This observation is par ticularly elucidated by calculating the slope Re (table I).…”
Section: Real Part Of Impedance (Resistance)supporting
confidence: 93%
See 1 more Smart Citation
“…The course of resist ance was independent of frequency, in agreement with other authors [21,27]. In our patients with obstructive lung diseases frequency dependence of resistance in creased with the degree of airway obstruc tion, a phenomenon also observed by others [8,14,18,21,27). This observation is par ticularly elucidated by calculating the slope Re (table I).…”
Section: Real Part Of Impedance (Resistance)supporting
confidence: 93%
“…In our normal subjects magnitude of re sistance determined at resonant frequency, 2.3 ± 0.4, was comparable to those ob tained by Fisher et al [4], Michaelson et al [21] , Stanescu et al [27] and Nagels et al [22] , and somewhat lower to that reported by Peslin et al [25]. The course of resist ance was independent of frequency, in agreement with other authors [21,27].…”
Section: Real Part Of Impedance (Resistance)supporting
confidence: 92%
“…A previous study in a small group (n=10) of grain workers showed similar outcome at 2 year follow-up [13]. Individual repeatability of R8 in our hands was slightly better compared to data published by NEILD et al [14] for impedance at 3 Hz (Z3Hz) (11.3%) or STANESCU et al [15] for resistance at 3-9 Hz (R3-9Hz) (12.0%) for short-term variability. Our coefficients of variation for R8 (10.5%), X8 (14.6%), and f0 (14.3%) would allow minimal detectable changes much smaller than those observed over 5 yrs in the present cohort.…”
Section: Discussionsupporting
confidence: 56%
“…In a previous study, the slope was found to be the only functional index which showed a significant difference between children exposed to urban air pollution and those of the same age and from the same area not having been exposed [7]. As suggested by STANESCU et al [25], it could represent an early manifestation of peripheral airway obstruction. Similar results were also reported by KJELDGAARD et al [26], and PESLIN et al [27], in asymptomatic smokers as compared with nonsmokers.…”
Section: Discussionmentioning
confidence: 80%